PENERAPAN MODEL MIND MAP DENGAN MEDIA GRAFIS DALAM PENINGKATAN PEMBELAJARAN IPS PADA SISWA KELAS IV SD - Lestari, Tri (KALAM CENDEKIA PGSD KEBUMEN, 2015)
Abstract: The Application of Mind Map Model using Graphic Media in Improving Social Science Learning for the Fourth Grade Students of Elementary School. The objectives of this research is to describe steps of Mind Map model using graphic media in improving social science learning for the fourth grade students of  elementary school.  This research is collaborative Classroom Action Research. Subjects of this research were 24 students of the fourth grade at SDN Kembaran. The results of this research show that the increase of learning results in each cycles. Percentage of students learning outcome in the first cycle 85,42%, in the second cycle increased to 89,2 %, and in the third cycles increased to 95,65 %. The conclusion of this research is the application of Mind Map model using graphic media can be improve social science learning for the fourth grade students of SDN Kembaran in the academic year of 2014/2015. Keyword: Mind Map, graphic,  learning, social science  Abstrak: Penerapan Model Mind Map dengan Media Grafis dalam Peningkatan Pembelajaran IPS pada Siswa Kelas IV SD. Tujuan dari penelitian ini adalah mendeskripsikan langkah-langkah model Mind Map dengan media grafis dalam peningkatan pembelajaran IPS pada siswa kelas IV SD. Penelitian ini adalah penelitian tindakan kelas kolaboratif. Subjek penelitian adalah 24 siswa kelas IV SDN Kembaran. Hasil penelitian menunjukkan adanya peningkatan hasil belajar di setiap siklusnya. Persentase hasil belajar siswa siklus I  85,42%, siklus II meningkat menjadi  89,2%, dan siklus III meningkat menjadi 95,65%. Simpulan dari penelitian ini adalah penerapan model Mind Map dengan media grafis dapat meningkatkan pembelajaran IPS pada siswa kelas IV SDN Kembaran tahun ajaran 2014/2015. Kata kunci: Mind Map, media grafis, pembelajaran, IPS